LRP-1 functionalized polymersomes enhance the efficacy of carnosine in experimental stroke - Kim, Eun Sun; Kim, Donghyun; Nyberg, Sophie; Poma, Alessandro; Cecchin, Denis; Jain, Saurabh A.; Kim, Kyeong A.; Shin, Young Jun; Kim, Eun Hye; Kim, Minyeong; Baek, Seung Hoon; Kim, Jin Ki; et al. (Scientific Reports, 2020)
Stroke is one of the commonest causes of death with limited treatment options. L-Carnosine has shown great promise as a neuroprotective agent in experimental stroke, but translation to the clinic is impeded by the large doses needed. We developed and evaluated the therapeutic potential of a novel delivery vehicle which encapsulated carnosine in lipoprotein receptor related protein-1 (LRP-1)-targeted functionalized polymersomes in experimental ischemic stroke. We found that following ischemic stroke, polymersomes encapsulating carnosine exhibited remarkable neuroprotective effects with a dose of carnosine 3 orders of magnitude lower than free carnosine. The LRP-1-targeted functionalization was essential for delivery of carnosine to the brain, as non-targeted carnosine polymersomes did not exhibit neuroprotection. Using Cy3 fluorescence in vivo imaging, we showed that unlike non-targeted carnosine polymersomes, LRP-1-targeted carriers accumulated in brain in a time dependent manner. Our findings suggest that these novel carriers have the ability to deliver neuroprotective cargo effectively to the brain.
Keywords: Animals; Brain Chemistry; Brain Ischemia; Carnosine; Disease Models, Animal; Drug Carriers; Drug Compounding; Low Density Lipoprotein Receptor-Related Protein-1; Male; Mice; Peptides; Rats; Stroke; Time Factors; Treatment Outcome